The private-public divide in international dispute resolution - Hess, Burkhard (Pocketbooks of the Hague Academy of International Law., 2018)
"This course addresses dispute resolution in international cases from the classical perspective of the private-public divide. The main focus relates to overlapping remedies available under private international and public international law. Nowadays, a multitude of courts and arbitral tribunals at different levels (domestic, international and transnational) is accessible to litigants in cross-border settings. There are three different areas where the private-public divide is applicable. The first pertains to lawsuits in civil courts involving foreign states, state enterprises and international organizations. The second area relates to the delineation between domestic and international remedies. The third area concerns the privatization of dispute settlement, especially in the context of private ordering. This study argues that the private-public divide still exists and cannot be given up. However, one must be aware that private and public international law have complementary functions in order to address adequately the multitude of disputes at both the cross-border and the international level. In this context, this divide can be used as an appropriate tool to explain the complementarity of private and public international law in the multilevel legal structure of a globalized world."